GENOTYPING OF YESINIA PESTIS ISOLATES RECOVERED DURING 1994 TO 2002 IN INDIA BY RESTRICTION FRAGMENT LENGTH POLYMORPHISM - MEENAKSHI KAPIL; REENA JAIN; URMIL TUTEJA (International Journal of Pharma and Bio Sciences, 2014)
Yersinia pestis, the causative agent of deadly disease Plague, is considered as a reemerging infectious disease and a significant bio-threat agent. The present study focused on the genetic variability analysis of Y. pestis isolates of Indian origin from different epidemiological context. A total of 29 Y. pestis isolates recovered from the rodents and pneumonic patients during 1994 outbreaks, pneumonic patients of 2002 Shimla outbreak and rodents trapped in Deccan Plateau during a surveillance activity carried out in 1998 were characterized by RFLP of 16S r DNA and of Insertion sequence elements (IS100, IS285 and IS1541) to understand the phylogenetic relatedness among them. The 16S rDNA revealed four distinct ribotypes, distinguishing the 18 Orientalis isolates of 1994 plague outbreaks from those of 7 obtained during plague surveillance activity in 1998. The three Antiqua isolates of 2002 plague outbreak clustered together separately and formed a distinct Ribotype other than those of Orientalis isolates and the lone Mediavalis isolate recovered during the surveillance. The IS100 with EcoRI restriction profile yielded a better discriminating profile than the other two IS probes. The RFLPs generated with IS285 and IS 1541 could group the strains according to their bio-vars. Phylogenetic analysis of IS100 RFLP suggested that there existed an appreciable variation among the isolates recovered during 1994 and 2002 outbreaks and also with the isolates obtained during surveillance conducted in 1998. The results distinctly connected the possible linkages between the Y. pestis strains resident in the endemic region and the ones that were associated with the 1994 plague outbreaks.